Iron metabolism following twice a day endurance exercise in female long-distance runners - Ishibashi, A.; Maeda, N.; Kojima, C.; Goto, K. (Nutrients, 2022)
Iron deficiency anemia (IDA) and iron deficiency (ID) are frequently observed among endurance athletes. The iron regulatory hormone hepcidin may be involved in IDA and/or ID. Endurance athletes incorporate multiple training sessions, but the influence of repeated bouts of endurance exercise within the same day on iron metabolism remains unclear. Therefore, the purpose of the present study was to investigate the influence of twice a day endurance exercise on iron metabolism, including the hepcidin level, in female long-distance runners. Thirteen female long-distance runners participated in this study. They completed the twice-a-day endurance exercise in the morning and afternoon. Blood samples were collected four times in total: at 06:00 (P0), 14:00 (P8), 20:00 (P14), and 06:00 the next day (P24). In addition to the blood variables, nutritional intake was assessed throughout the exercise day. Serum hepcidin levels were significantly elevated (compared to P0) until the following morning (P24). Moreover, dietary analysis revealed that subjects consumed a low volume of carbohydrates (<6 g/kg body mass/day). In conclusion, twice a day endurance exercise resulted in significant elevation of serum hepcidin level 24 h after completion of the exercise in female long-distance runners. Therefore, athletes with a high risk of anemia should pay attention to training frequency and nutritional intake in order to maintain optimal iron metabolism.